Methods of developing special competencies of future technological education teachers - Karimov Arif Oblokul Qizi; Nizamov Shakir Shukurovich; Yoldashev Mirjalal Kasim Qizi (Genius Journals, 2023)
Currently, training of future teachers at the level of modern requirements remains one of the urgent issues. This article provides feedback on the development of special competencies of the future technological education teacher (design, Arduino programming, 3D modeling, production)
Keywords: competence; technology; robotics; design